Tren Blended Learning untuk Pengembangan Keterampilan Matematika Siswa - Maria Shelyn Fobia; Juliana M. H. Nenohai; Damianus D. Samo (Universitas Nusa Cendana, 2021)
This review aims to describe the model, characteristics, and design of blended learning, to describe the trend of research blended learning in supporting the development of students' mathematical thinking skills and to provide recommendations for blended learning in supporting the development of students' mathematical thinking skills in the future. The method used in this paper is an article review method which is carried out in three stages, namely identifying keywords related to blended learning in developing mathematical thinking skills, article search strategies, and analyzing articles. Blended learning is a combination of learning patterns, between face-to-face learning and online learning. The trend of Blended learning is carried out with online learning and face-to-face learning in class is carried out alternately (rotational model), using various LMS. The results of the article analysis show that the blended learning stage can develop students' mathematical thinking skills, namely the seeking of information stage students are directed to think critically. At this stage students are more motivated and independent in finding or accessing materials online. Then at the stage of acquisition of information and synthesizing of knowledge, students are directed to solve problems, use mathematical understanding skills, reasoning, connection and representation skills, communication and collaboration, and think critically through discussions, presentations, and work on practice questions. In addition, students look more enthusiastic and motivated because it is adjusted to their learning style and learning speed and students are directed to be independent in learning the material. The researcher recommends a blended learning design using the flipped classroom model with online learning using the Moodle LMS in which each stage of blended learning, students are directed to rely on mathematical thinking skills. Keywords : Blended learning and mathematical thinking skills